Transboundary cooperation and mechanisms for Maritime Spatial Planning implementation. SIMNORAT project. (May 2021) - Gómez-Ballesteros, M.; Cervera - Núñez, C.; Campillos-Llanos, M.; Quintela, A.; Sousa, L.; Marques, M.; Alves, F.L.; Murciano, C.; Alloncle, N.; Sala, P.; Lloret, A.; Simão, A.P.; et al.
Abstract: Maritime Spatial Planning (MSP) is gaining importance as a new process for the governance of seas and oceans, as maritime nations exercise greater management over their territorial waters and, in many cases, over exclusive economic zones that span a larger area. The purpose of this planning is to reverse the environmental degradation of the seas and facilitate the sustainable use of marine resources, both for mature uses such as fishing and navigation, and for emergent uses, including renewable energies and mariculture. In Europe, the Directive 2014/89/EU of the European Parliament and of the Council of 23 July 2014 establishing a framework for maritime spatial planning oblige coastal Member States to develop maritime spatial plans at the latest by 31st March 2021. To help in that process, countries have at their disposal a set of existing instruments, including research projects, supporting guidelines, recommendations and sets of tools and data, as the SIMNORAT project, co-funded by the EC – DG Maritime Affairs and Fisheries (DG MARE). This paper presents best practices developed in this project on technical, scientific, and social aspects of MSP to overcome barriers of MSPD implementation testing effective cooperation on transboundary areas and providing a set of cross-cutting MSP related recommendations to foster collaborative efforts and to improve the overall transboundary dimension of the MSP Directive.